Strategic development model for priority MSMEs in Jambi City using the VIKOR-STRAS framework - Yuvanda, Sesraria; Rachmad R., Muhammad; Zulfanetty, Zulfanetty; Ihsan, Mohammad; Nurkodri, Moh. Sahroni (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2026)
Micro, small, and medium enterprises (MSMEs) play a vital role in the regional economy of Jambi City; however, the identification of priority sectors and the formulation of sector-specific development strategies remain insufficiently addressed. This study aims to identify priority MSME sectors and formulate targeted development strategies to support regional economic development. The study employs the VIšekriterijumsko KOmpromisno Rangiranje (VIKOR) multi-criteria decision-making method to rank MSME sectors based on eight evaluation criteria: business age, owner education, business experience, income, number of employees, business capital, working hours, and promotional media. The research combines secondary data analysis, field surveys, and in-depth interviews, using a purposive sample of 204 MSMEs across eight business sectors. The VIKOR-STRAS framework is subsequently applied to translate the ranking results into sector-specific development strategies. The findings indicate that the creative industry, culinary, and information technology sectors represent the three highest development priorities. Based on the sectoral performance profiles, the proposed strategies emphasize improving access to finance and market opportunities, strengthening product innovation and digital marketing, and enhancing digital infrastructure, technology adoption, and human resource capacity. The principal contribution of this study is the integration of the VIKOR method with the VIKOR-STRAS framework to translate multi-criteria ranking results into practical development strategies systematically. Theoretically, the study extends the application of multi-criteria decision-making by linking compromise-based prioritization with sector-specific strategy formulation. In practice, it provides local policymakers with a structured, evidence-based decision-support framework for designing targeted, sector-sensitive MSME development policies.